BENEFICIAL OUTCOMES AFTER COMBINED THERAPY WITH AZATHIOPRINE AND PIOGLITAZONE IN PRECLINICAL ARTHRITIC MODELS - BABU PRATAP, VEERESH; VARLA, SOUNDARYA; M, GANGA RAJU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study was designed to investigate the antioxidant and anti-arthritic activities of azathioprine-pioglitazone combination therapy to check whether it has an add on benefit over monotherapy with azathioprine or pioglitazone on disease activity in rodent models. Methods: The antioxidant activity of test drugs and their combination was screened by H2O2 and nitric oxide scavenging assays. They were further evaluated for anti-arthritic activity using in vitro models such as protein denaturation and membrane stabilization and in vivo methods such as formaldehyde and complete Freund’s adjuvant (CFA)-induced arthritis. Results: The combination of test drugs showed better inhibition of free radicals in both H2O2 and nitric oxide scavenging assay than individual counterparts revealing its potential antioxidant activity. They also showed significant inhibition of protein denaturation and proliferation of the red blood cell in in vitro models. The test drugs showed significant inhibition of the paw volume in both the formaldehyde and CFA-induced arthritis along with reverting the altered biochemical parameters. These findings were corroborated by radiological and histopathological studies. Conclusions: Combination of azathioprine and pioglitazone exhibited better antioxidant and anti-arthritic effect than the individual drugs showing synergistic interaction between them.